Adaptive aspects of maximizing in times of COVID-19: coping efforts linking maximization to well-being - Jun, Young Joo; Choi, Incheol; Kim, Joo Hyun (Frontiers in Psychology, 2024)
Introduction Maximization, the tendency to make the best choices by thoroughly searching and comparing alternatives, has long been considered a negative correlate of well-being. However, recently, it was proposed that having a maximizing tendency can lead to better coping efforts in some stressful situations and thus could be more adaptive. The objective of the present research was to demonstrate positive features of maximization and identify the coping strategies that mediate the relationship between maximization and well-being during the COVID-19 pandemic. Methods A sample of 3,493 participants responded to an online survey from January 20 to October 11 of 2020. The 13-item Maximization Scale assessed individuals’ maximizing tendency in terms of the maximization index and its three subdimensions (i.e., high standards, alternative search, and decision difficulty). The use of four coping strategies (i.e., preventive measures, cognitive appraisal, self-distraction, and social connection) during the COVID-19 pandemic was assessed. Hedonic and eudaimonic aspects of well-being were measured. We developed a mediation model and examined both whether there was an indirect link between maximization and well-being through the coping strategies and whether there was a direct link between maximization and well-being. Results Path analysis revealed negative direct associations between maximization measures (i.e., an index and three subdimensions) and well-being. In addition, significant indirect paths were found with varying directions depending on maximization dimensions and coping strategy types. There were positive indirect associations between the maximization index and well-being via preventive measures, between high standards and well-being through preventive measures and cognitive appraisal, and between alternative search and well-being through self-distraction and social connection. Negative indirect associations were found between decision difficulty and well-being through cognitive appraisal, self-distraction, and social connection. Discussion The current study confirmed the existence of inconsistent mediation effects between maximization and well-being via coping and highlighted coping efforts as one of the positive aspects of maximization. Discussion addressed the double-edged effect of maximization on well-being and its beneficial nature in times of distress. Future studies should examine other potential situations and moderators that can delineate maximization’s various characteristics with a longitudinal design and samples from diverse backgrounds.